HUBUNGAN ASUPAN ZAT GIZI PROTEIN DENGAN STATUS GIZI BALITA USIA 6-24 BULAN DI RW 2 WILAYAH PUSKESMAS BATUA KOTA MAKASSAR - Manji Lala; donna Inrivianthy; fatmawaty Suaib (Jurusan Gizi Poltekkes Kemenkes Makassar, 2017)
Backgrounds:Nutrition problem is a health problem that influenced by many factors. Malnuorished toddlers has slow growth and development than the healthy toddler, if the problem has not solve it can caused health problem until the toddler become mature. Aged of 0-24 months is a golden period of growth and development.Objectives:This research aims to determine the relationship of protein intake with toddler’s nutritional status aged 6-24 months in RW 2 Puskesmas Batua Area Makassar City.Methods:This research is an descriptive-analytic with cross sectional study design. The population were all the toddler aged 6-24 months in RW 2 Puskesmas Batua. Sample was selected by random sampling method. Total sample were 35 toddler. The statistical analysis test that used was chi square with the degree of significancy 0,05.Results:The results showed that protein intake 17 toddler was good (48,6%) compared to the others (51,4%). Based on data analysis found that there were not significant relationship between protein intake with toddler’s nutritional status aged 6-24 months based on bb/u index with p:0,125, tb/u index with p: 0,380 and bb/tb index with p: 0,323.Conclusions:There were not significant relationship between protein intake with toddler’s nutritional status aged 6-24 months in RW 2 Puskesmas Batua area Makassar cityKeywords: Protein, Nutritional status and ToddlerHUBUNGAN ASUPAN ZAT GIZI PROTEIN DENGAN STATUS GIZI BALITA USIA 6-24 BULAN DI RW 2 WILAYAH PUSKESMAS BATUA KOTA MAKASSAR